Swimming against the tide in STEM education and gender equality: a problem of recruitment or retention in Malaysia - Goy, Siew Ching; Wong, Yut Lin; Low, Wah Yun; Noor, Siti Nurani Mohd; Fazli-Khalaf, Zahra; Onyeneho, Nkechi; Daniel, Esther Gnanamalar Sarojini; Azizan, Suzana Ariff; Hasbullah, Maisarah; Uzoigwe, Anthonia Ginika (Taylor & Francis, 2018)
Science, technology, engineering and mathematics (STEM) is acknowledged as one of the key drivers of technological innovation. Malaysian women join the educational pipeline as equals to their male counterparts. Nevertheless, women are persistently under-represented in technology and engineering, but over-represented in other STEM fields. Using data provided by the Malaysian Ministry of Higher Education, our results suggest that under-representation of women in engineering was attributed to low recruitment at the point of entry. Such a finding thus begs the question as to why women were not recruited into engineering. Malaysian policymakers and educators need to address under-representation of women in order to achieve gender equality in STEM, as part of the goals of Millennium Development and Vision 2020; to become a nation that is competent, confident and innovative in harnessing and advancing science and technology.